Community Partnership Empowerment Through Utilizing Waste Glass for Construction Products: Pemberdayaan Kemitraan Masyarakat Melalui Pemanfaatan Limbah Kaca Menjadi Produk Konstruksi - Rahmawati Cut; Iqbal Iqbal; Meliyana Meliyana; Muhtadin Muhtadin; Muhammad Faisal; Amri Amin; Nasruddin Nasruddin; Abdul Hidayat (Universitas Lancang Kuning, 2023)
Waste glass constitutes significant landfill waste, leading to environmental concerns. Considering its chemical composition, glass powder contains 50% to 60% silica, making it suitable for construction materials. Consequently, this community service initiative introduced waste glass as a building material, serving as a partial substitute for sand in construction products. In addition, the activity involved teaching partners how to create castings/road gates utilizing waste glass. The target partners in this activity were productive business groups engaged in selling wind holes, well rings, rosters, and similar products. The approach applied involved socialization and hands-on practices at the partner's premises. The program's success was obtained through interviews and product compressive strength tests with the partners. The outcomes demonstrate the partners' keen interest in the activity, their understanding of the benefits of utilizing waste glass as a partial sand replacement, and their ability to create products. Notably, the compressive strength of the products created with the partners ranged from 24.72 MPa to 30.84 MPa, aligning with the SNI 03-2442-1991 standard for road curbs (30 MPa). The activity positively impacted the partners, enhancing their business prospects and contributing to environmental sustainability. The training helps in enhancing the partners' skills and capabilities.